2011
DOI: 10.1212/wnl.0b013e318205d521
|View full text |Cite
|
Sign up to set email alerts
|

Increased temporolimbic cortical folding complexity in temporal lobe epilepsy

Abstract: Objective: Converging evidence suggests that abnormalities of brain development may play a role in the pathogenesis of temporal lobe epilepsy (TLE). As sulco-gyral patterns are thought to be a footprint of cortical development, we set out to quantitatively map folding complexity across the neocortex in TLE. Additionally, we tested whether there was a relationship between cortical complexity and features of hippocampal maldevelopment, commonly referred to as malrotation. Methods:To quantify folding complexity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 39 publications
6
67
0
Order By: Relevance
“…Similar to previous studies on cortical thickness, the distribution of effects was relatively broad but had a predominance of effects in nearby frontal, temporal and limbic regions (Lin et al, 2007;Bernhardt et al, 2010;Kemmotsu et al, 2011). Additionally, measures of curvature and folding were found to be abnormal in ipsilateral temporal and frontal cortices, concordant with prior work (Voets et al, 2011;Alhusaini et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous studies on cortical thickness, the distribution of effects was relatively broad but had a predominance of effects in nearby frontal, temporal and limbic regions (Lin et al, 2007;Bernhardt et al, 2010;Kemmotsu et al, 2011). Additionally, measures of curvature and folding were found to be abnormal in ipsilateral temporal and frontal cortices, concordant with prior work (Voets et al, 2011;Alhusaini et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…These findings are present in TLE patients with and without MTS but have been shown to be stronger in patients with MTS (Labate et al, 2011). Additionally, these methods allow for measurements of cortical folding and complexity, which have also been reported to be abnormal in individuals with TLE and MTS, particularly in ipsilateral temporal and frontal cortices (Voets et al, 2011;Alhusaini et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Previous evidence suggests that TLE may be the result of a neuro-developmental disorder (Voets et al, 2011). One explanation for these findings may be that those with TLE may have more uncontrolled epilepsy.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that maldevelopment in the cortex may lead to persistent changes in network properties within the brain, resulting in TLE. A recent study by Voets and colleagues (2011) explored the relationship of hippocampal malrotation, which is rarely found in individuals without seizures, and cortical abnormalities with TLE (Voets, Bernhardt, Kim, Yoon, & Bernasconi, 2011). The researchers found that TLE was associated with increased folding of the temporal limbic and neocortex, which the researchers' state is suggestive of a common neuro-developmental phenotype with maldevelopment of the temporal lobes, as an important factor in the development of TLE.…”
Section: Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation